Development and validation of a prognostic nomogram for early hepatocellular carcinoma treated with microwave ablation - Zhang, Jing; Guo, Guanya; Li, Tao; Guo, Changcun; Han, Ying; Zhou, Xinmin (Frontiers in Oncology, 2025)
ObjectiveAn effective model for risk stratification and prognostic assessment of early hepatocellular carcinoma (HCC) patients following microwave ablation (MWA) is lacking in clinical practice. The aim of this study is to develop and validate a prognostic model specifically for these patients.MethodsBetween January 2008 and December 2018, 345 treatment-naïve patients with HCC conforming to the Milan criteria who underwent MWA were enrolled and randomly assigned to the training (n=209) and validation (n=136) cohorts. The nomogram model was constructed based on the predictors assessed by the multivariate Cox proportional hazards model and validated. Predictive accuracy and discriminative ability were further evaluated and compared with other prognostic models.ResultsAfter a median follow-up of 59.0 months, 52.5% (187/356) of the patients had died. Prognostic factors for overall survival (OS) were α-fetoprotein (AFP), albumin-bilirubin (ALBI) score, platelets, and ablation margins, which generated the nomograms. The nomogram model consistently achieved good calibration and discriminatory ability with a concordance index of 0.64 (95% confidence interval (CI): 0.59-0.69) and 0.69 (95% CI: 0.63-0.75) in both the training and validation cohorts. The performance of the nomogram model also outperformed other prognostic models. By using the nomogram model, the patient population could be correctly divided into low- and high-risk strata presenting significantly different median OS of 105.0 (95% CI: 84.1-125.9) months, and 45.0 (95% CI: 28.0-62.0) months, respectively.ConclusionThe nomogram model based on AFP, PLT, ablation margins, and ALBI score was a simple visualization model that could stratify patients with early‐stage HCC after MWA and predict individualized long-term survival with favorable performance.